2017
DOI: 10.5606/tgkdc.dergisi.2017.12967
|View full text |Cite
|
Sign up to set email alerts
|

What fate befalls the congress proceedings? Conversion rates of National Thoracic Surgery Congress proceedings into international publications

Abstract: ÖZAmaç: Bu çalışmada, Ulusal Göğüs Cerrahisi Kongresi'nde sunulan bildirilerin takip eden dört yıl içinde bilimsel dergilerde yayına dönüştürülme oranları belirlendi ve Türkiye'de yayımlanan bu bildiri oranları ile ilişkili değişkenler incelendi. Çalışm a planı:PubMed veri tabanı kullanılarak, 2011 yılında VI. Ulusal Göğüs Cerrahisi Kongresi'nde sunulan ve uluslararası hakemli dergilerde ve Türk Kalp Damar Cerrahisi Derneği ve Türk Göğüs Cerrahisi Derneği'nin resmi yayını Türk Göğüs Kalp Damar Cerrahisi Dergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
(18 reference statements)
2
6
1
Order By: Relevance
“…In our study, we observed a rearrangement in the author list in approximately half of the presentations when published, and nearly one-third of this was concerned with the first author. This finding was similar with that in the other national congresses ( 33 ). It may be presumed that after the presentation at meetings, some of the studies had an improvement process, leading to a revision in the author list.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we observed a rearrangement in the author list in approximately half of the presentations when published, and nearly one-third of this was concerned with the first author. This finding was similar with that in the other national congresses ( 33 ). It may be presumed that after the presentation at meetings, some of the studies had an improvement process, leading to a revision in the author list.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, some of the researches from state hospitals might have been sent by physicians who started their compulsory service in state hospitals after training; their studies should be originated from their residencies; and it can be assumed that universities even have more contribution to this rate. [9] The publication rate of presentations from training and research hospitals was lower, and this could be regarding various reasons, as less time assignation for academic and research studies compared to universities, distinction in training methods, and retarded supervision of the publication course. Also, it should be kept in mind that the accomplishment of new Health Sciences University and direct interaction of training and research hospitals with this newer settlement may bring positive impact on research activities to physicians and residents who are members of these hospitals, consequently, increasing their publication rates as expected.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology used in this study, involving PubMed and Google Scholar search, seems like those used in corresponding researches. [5][6][7][8][9]15,16] Numerous investigations do not define the search technique methodology in detailed and do not distinguish between the several factors. Nonetheless, we did not reach the authors of non-published abstracts and we were unable to determine an accurate reason for not submitting their work for publication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations